Implementation of Assessment Based Character For Enhancing Social Value Student Class X at Swadhipa High School Natar, South Lampung: A Classroom Action Research in Sociology Learning - Mas Ayu, Sovia; Sari, Putri Permata (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2026)
Demands education 21st century emphasizes importance strengthening character besides achievements academic , but practice assessment at school Still dominant oriented cognitive so that internalization mark character not optimal. Research This aim optimizing assessment based on character in learning Sociology through Classroom Action Research (CAR) that was implemented in two cycles against 30 students class X of Swadhipa High School Natar , South Lampung. Every cycle covering stage planning , action , observation , and reflection with intervention in the form of learning collaborative and projects based issue social assessors indicator Work same , responsibility responsibility , empathy , honesty , and caring social . Data collected through observation sheet evaluation characters , and documentation , then analyzed in a way descriptive quantitative and qualitative . Research results show improvement significant internalization character student from 60.7% in Cycle I to 82.0% in Cycle II, exceeding criteria success (≥75%), with Work The same as aspect highest (86.7%). Findings This confirm that assessment is based on character effective in strengthen strengthening character student in learning Sociology . Implications study This show that application of assessment based on character can become an assessment strategy integrative alternative for teachers in evaluate at a time grow values social student through learning contextual and reflective in the classroom.